RESPON INVESTOR TERHADAP PROGRAM TAX AMNESTY BAGI PERUSAHAAN GO PUBLIC - MUSTOFA, ARIF (Jurnal Akuntansi AKUNESA, 2018)
The government has dismissed the policy of tax pardons in the form of nonimposition of sanctions and penalties for taxpayers by revealing assets that have not previously been disclosed. Companies participating in the program are expected to be good signals for investors who will be reflected by the increasing trading volume activity. This research aims to examine whether there are differences in the trading volume activity before and after the public company following the tax amnesty. It also examine there is a difference between the public company that follow or not. This research used non-parametric statistic that is wilcoxon signed ranks test and mann-whitney test. The result showed that there is no difference of trading volume activity before and after the tax amnesty program and there is no difference between tax amnesty companies anda non-tax amnesty companies.